The Role of Educational Personnel in Supporting Madrasah Governance at MTsN 3 Aceh Tamiang - Nazla Sofi Adinda; Syafri Fadillah Marpaung (DIDAKTIKA, 2026)
This study aims to analyze the role of educational staff in supporting madrasah governance at MTsN 3 Aceh Tamiang, identify the challenges they face, and evaluate the effectiveness of collaboration between educational staff and teachers in improving the quality of educational services. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and documentation involving the head of the madrasah, administrative staff, librarians, and laboratory personnel. Data analysis was conducted through data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings indicate that educational staff play a strategic role in supporting madrasah governance, particularly in administrative management, academic services, and the management of facilities and infrastructure. Effective administrative performance contributes to operational efficiency and supports the learning process. However, several challenges were identified, including limited human resources, insufficient competency development, and suboptimal coordination. Effective collaboration between educational staff and teachers significantly enhances service quality and fosters a conducive learning environment. Therefore, optimizing the role of educational staff through competency development and strengthened coordination is essential to achieving effective, transparent, and accountable madrasah governance.